MODEL PERTUTURAN POLITIKUS DALAM PEMILU DI INDONESIA: KAJIAN SOSIOPRAGMATIK (POLITICIAN SPEECH MODEL IN INDONESIA ELECTION: SOCIOPRAGMATICS STUDY) - Wini Tarmini; Imam Safi'i; Nani Solihati (Metalingua: Jurnal Penelitian Bahasa, 2020)
This research aimed to describe the politician speech model in 2019 electioncampaign in Indonesia using qualitative research design and descriptive method. Data were colleted by documentation/literature study and recording. The data was processed using interactive analysis of Miles Huberman’s. The results showed that the types of electoral politicians’ speech in Indonesia were illocution which contained representative, directive, expressive, commissive, and declarative speeches. From the total of 119 speeches it was found that there were 54 expressive speeches, 30 representative speeches, 17 declarative speeches, 12 directive speechess, and 6 commissive speeches. Thus, in the political campaign of 2019, the politicians tended to use expressive speech which was interpreted as an evaluation of the things mentioned and the speech tended to blame and to criticize. From this description it can be concluded that the politician speech in the 2019 political campaign, in political language context related with socio-psychological aspect of Indonesian society in 2019 election campaign. AbstrakKajian ini bertujuan mendeskripsikan model pertuturan politikus dalam kampanye pemilu tahun 2019 di Indonesia menggunakan desain penelitian kualitatif dengan metode deskriptif. Pengumpulan data menggunakan metode kepustakaan/dokumentasi dan rekaman. Pengolahan data menggunakan model analisis interaktif Miles Huberman. Hasil penelitian menunjukkan bahwa jenis pertuturan politikus dalam pemilu di Indonesia adalah pertuturan ilokusi yang meliputi pertuturan representatif, direktif, ekspresif, komisif, dan deklaratif. Dari 119 kutipan ditemukan pertuturan ekspresif sebanyak 54, representatif sebanyak 30, deklaratif sebanyak 17,direktif sebanyak12, dan pertuturan komisif sebanyak 6. Dengan demikian, dalam kampanye politik tahun 2019, politikus dalam pemilu cenderung menggunakan pertuturan ekspresif yang tuturannya diartikan sebagai evaluasi tentang hal yang disebutkan dan tuturan tersebut cenderung “menyalahkan” dan “mengkritik”. Dari gambaran tersebut dapat disimpulkan model pertuturan politikus dalam kampanye pemilu 2019, dalam konteks bahasa politik, berkaitan dengan aspek sosial-psikologis masyarakat Indonesia.